Propuesta para el Diseño de la Documentación del Sistema de Gestión Ambiental con Base en la NTC ISO 14001:2015 para la Empresa de Pinturas Química Mundial en la Ciudad de Bogotá (2021)
The company Química Mundial is a family business, dedicated to the manufacture and marketing of a wide portfolio of paint products, located in the city of Bogotá - Colombia in the sixth town (Tunjuelito), founded in June 2016. This company has flaws in the management of the waste management that it generates in its production processes, due to this the students of the Faculty of Industrial Engineering of the Antonio Nariño University, design a documentary proposal of the environmental management system (SGA) based on in the ISO 14001 standard of 2015, to achieve this proposal the first thing that is carried out is a diagnosis, to detail point-by-point compliance with the standard by the company, resulting in a low percentage of 1.5% of compliance, after analyzing this diagnosis, we proceed to the execution of the objectives such as: analyze the internal and external context of the organization, establish risk management, evaluatending and assessing the environmental impacts, preparing the documentary proposal based on the ISO 14001: 2015 Standard and analyzing the cost benefit of the project, for the development of these objectives the following tools are used: PHVA Cycle, DOFA Matrix, Leopold Matrix, Storm Tool , and the Guide for the implementation of the standard for PYMES